Structure, properties and potential applications of phytoglycogen and waxy starch subjected to carboxymethylation - Liu, Yao; Lu, Keyu; Hu, Xiuting; Jin, Zhengyu; Miao, Ming (Carbohydrate polymers, 2020)
•Structure and properties for different CM-starches were investigated.•DS of CM-PG was higher than that of CM-WS under equivalent modification conditions.•The Mw increased for CM-PG with increasing DS whereas Rz was nearly constant.•Carboxymethylation modification resulted in a greater increase of SDS and RS.•Tailor-made CM-PG can be used as a potential carrier for bioactive ingredients. The structure and properties of phytoglycogen (PG) and waxy starch (WS) from different mutants subjected to carboxymethylation (CM) were investigated. FT-IR analysis confirmed the carboxymethylation of PG and WS. The degree of substitution (DS) increased with increasing of the ratio of monochloroacetic acid to anhydroglucose unit, while DS of CM-PG was higher than that of CM-WS using equivalent modification conditions. The weight-average molecular weight (Mw) and radius of gyration (Rz) of CM-WS increased with the DS, whereas the Mw increased and Rz was nearly constant for CM-PG. The zeta-potential of CM-WS reduced and the viscosity increased significantly as DS increased, while the viscosity of CM-PG was remarkably lower than that of CM-WS with equivalent of DS. The increase of DS in CM-starches resulted in a substantial reduction of RDS accompanied by the increase of SDS and RS. The results revealed the promising application of CM-PG as a potential carrier system for bioactive ingredients.